P91 Direct thrombectomy versus intravenous bridging – the benefit of alteplase depends on ASPECTS. (29th August 2022) - Broocks, G; Meyer, L; Bechstein, M; Kemmling, A; Hanning, U; Fiehler, J; Faizy, TD
Abstract : Introduction and aim of this study: Baseline variables could be used to guide the administration of additional intravenous alteplase (IVT) before mechanical thrombectomy (MT). The aim of this study was todetermine how baseline imaging and demographic parameters modify the effect of IVT on clinical outcomes. We hypothesized that the extent of early ischemic changes modify the effect of IVT on functional outcomes in stroke patients undergoing MT. Methods: Multicenter cohort study of stroke patients triaged by multimodal-CT undergoing MT treatment. Inverse-probability weighting analysis (IPW) was used to assess the treatment effect of IVT adjusted for baseline variables. Multivariable logistic regression analysis with IPW-weighting and interaction terms for IVT was performed to predict functional independence (mRS 0–2 at 90-days). Results: 720 patients were included, of which 366 (51%) received IVT. In IPW, the treatment effect of IVT on outcome (mRS 0–2) distinctively varied according to the ASPECTS subgroup (ASPECTS 9–10: +15%, ASPECTS 6–8: +7%, ASPECTS <6: -11%).In multivariable logistic regression analysis, IVT was independently associated with functional independence (aOR: 1.57, 95%CI: 1.16–2.14, p=0.003) and the interaction term was significant for ASPECTS and IVT revealing that IVT was only significantly associated with better outcomes in patients with higher ASPECTS. No other significant baseline variable interaction terms were identified. Conclusion: ASPECTS was the only baseline variable that showed a significant interaction with IVT for outcome prediction. The application of IVT in patients with an ASPECTS of <6 might have detrimental effects on outcome and may only be considered carefully. References: Chandra RV, Leslie-Mazwi TM, Mehta BP, et al . Does the Use of IV TPA in the Current Era of Rapid and Predictable Recanalization by Mechanical Embolectomy Represent Good Value? J Neurointerv Surg 2016 May;8 (5):443–6. Turc G, Tsivgoulis G, Audebert HJ, et al . European Stroke Organisation (ESO)-European Society for Minimally Invasive Neurological Therapy (Esmint) Expedited Recommendation on Indication for Intravenous Thrombolysis before Mechanical Thrombectomy in Patients with Acute Ischemic Stroke and Anterior Circulation Large Vessel Occlusion. J Neurointerv Surg 2022 Mar;14 (3):209. Do you have any conflict of interest to declare? : No